Fabrication of novel pyramid-textured and nanostructured Cu2O/Si heterojunctions. Issue 4 (25th November 2020) - Ma, Ji; Wang, Zhiwei; Qi, Hao; Pan, Peng; Lang, Xianzhong; He, Zuming; Tang, Bin; Su, Jiangbin
Abstract : To enhance the performances of copper (I) oxide (Cu2 O)/silicon (Si) heterojunctions, it is crucial to improve their interface quality and control their surface microstructures. Here, two kinds of pyramid-textured and nanostructured copper (I) oxide/silicon heterojunctions were fabricated by adjusting the substrate bias during magnetron sputtering. Scanning electron microscopy, X-ray diffraction, ultraviolet (UV)–visible spectroscopy and I – U tests were performed to characterize their morphology, structure and optical and electrical properties. It was found that copper (I) oxide/silicon heterojunctions exhibited high adhesion quality at the interface and a controllable shape of building blocks of copper (I) oxide thin films. The effects of substrate bias on the morphology and deposition rate of copper (I) oxide thin films were further revealed. Relative to the case of +50 V, copper (I) oxide thin films deposited at +150 V showed a more significant (111)-preferred orientation and a much lower reflectance, particularly in the UV region. In addition, the I – U characteristic test results showed that the forward conduction voltages are 1.85 and 0.5 V and the reverse breakdown voltages are −19 and −17 V for the copper (I) oxide/silicon heterojunctions prepared at V s = +50 V and V s = +150 V, respectively. This work has important guiding significance for the preparation of copper (I) oxide/silicon heterojunctions with high interface quality and controllable surface microstructures. It also suggests that copper (I) oxide/silicon heterojunctions may have potential applications in the fields of UV resistance, UV sensors, solar cells and diodes.